Learning in the New Normal: Positive convergence of technology, quality, and sustainability - Ang, Merceditas O (GHMJ (Global Health Management Journal), 2022)
All of us are affected by the COVID-19 pandemic that caused disruptions in education, healthcare, economy, and travels. Likewise, it is impacting the way we live, study, work, think, and interact. This perspectives provide how the education sector is affacted by the outbreak, and how the online learning has catapulted into the forefront due to the restriction of face-to-face classes.  Communication is very important and vital during this pandemic. We need to communicate clearly, positively, and effectively. In the digital platform of teaching and learning, the teacher needs to be creative and innovative in communicating, to get the interest and attention of the students, thus, make the learning process more engaging and interactive. In this paper, the author writes the challenges for conducting online learning in the new normal that involving the three vital elements: Technology, Quality, and Sustainability.